Blood Glucose Fasting Increasing Levels Comparison After Consumption Stevia and Granulated Sugar in Healthy Individuals - Komang Krisna Dewi; Sinta Deviyanti; Nurani Hayati (Sriwijaya Journal of Dentistry, 2025)
Introduction: Increased blood glucose levels are caused by a lifestyle that involves excessive consumption of foods and drinks containing sweeteners. Stevia Rebaudiana Bertoni leaves are a natural ingredient that can be used as a natural sweetener because it contains stevioside and rebaudioside A with a sweet taste effect that is 200 to 300 times higher than the sucrose found in granulated sugar. However, there are still few studies reporting comparative data on fasting blood glucose levels after consuming natural Stevia and granulated sugar as a sweetener in healthy individuals. Objective: To compare the increase in fasting blood glucose levels after consuming Stevia and granulated sugar as sweeteners in healthy individuals. Method: Experimental research with a pretest-posttest with control group design carried out using purposive sampling, research subjects were 40 people aged 17-23 years who were asked to fast for 8-10 hours. Fasting blood glucose levels were measured before consuming powdered and liquid Stevia, granulated sugar and mineral water as a control and further measurements were carried out 45 minutes after treatment. Results: The highest increase in fasting blood glucose levels occurred in subjects who consumed granulated sugar solution, namely 15.8 mg/dL, followed by subjects who consumed liquid Stevia solution at 6.6 mg/dL, and the lowest in subjects who consumed powdered Stevia solution. Stevia solution is 5.6 mg/dL. Conclusion: There is a significant difference in blood glucose levels before and after the treatment of consuming powdered Stevia, liquid Stevia and granulated sugar sweetener. The increase in fasting blood glucose levels after consuming powdered or liquid Stevia sweetener was significantly lower than granulated sugar sweetener. Keywords: Stevia, Granulated Sugar, Blood Glucose Levels